Chapter 5 Introduction to Temple Rituals - Kulshreshtha, Salila (Taylor & Francis, 2023)
The Introduction will discuss secondary writings on temples as a place for public worship of the deity which is done through several daily, monthly and annual rituals performed in different spaces in the temple complex. Moving away from the ethnographic and textual studies of Hindu rituals which focus on contemporary ritual praxis, this chapter examines temple rituals in a historical context within the different spaces in the temple precinct such as the various tanks, courtyards and mandapas. The chapter also examines the changing context of temple rituals by studying the materiality of temple spaces and argues how the temple complex itself was organized and renovated to accommodate the varied rituals. The chapter will finally explore how through the practice of rituals the temple is embedded in its surrounding cultural landscape.